One-Vector System for Multiplexed CRISPR/Cas9 against Hepatitis B Virus cccDNA Utilizing High-Capacity Adenoviral Vectors - Maren Schiwon; Eric Ehrke-Schulz; Andreas Oswald; Thorsten Bergmann; Thomas Michler; Ulrike Protzer; Anja Ehrhardt (Elsevier, 2018)
High-capacity adenoviral vectors (HCAdVs) devoid of all coding genes are powerful tools to deliver large DNA cargos into cells. Here HCAdVs were designed to deliver a multiplexed complete CRISPR/Cas9 nuclease system or a complete pair of transcription activator-like effector nucleases (TALENs) directed against the hepatitis B virus (HBV) genome. HBV, which remains a serious global health burden, forms covalently closed circular DNA (cccDNA) as a persistent DNA species in infected cells. This cccDNA promotes the chronic carrier status, and it represents a major hurdle in the treatment of chronic HBV infection. To date, only one study demonstrated viral delivery of a CRISPR/Cas9 system and a single guide RNA (gRNA) directed against HBV by adeno-associated viral (AAV) vectors. The advancement of this study is the co-delivery of multiple gRNA expression cassettes along with the Cas9 expression cassette in one HCAdV. Treatment of HBV infection models resulted in a significant reduction of HBV antigen production and the introduction of mutations into the HBV genome. In the transduction experiments, the HBV genome, including the HBV cccDNA, was degraded by the CRISPR/Cas9 system. In contrast, the combination of two parts of a TALEN pair in one vector could not be proven to yield an active system. In conclusion, we successfully delivered the CRISPR/Cas9 system containing three gRNAs using HCAdV, and we demonstrated its antiviral effect. Keywords: chronic HBV infection, multiplexed CRISPR/Cas9, high-capacity adenovirus, cccDNA degradation